An algorithm to reduce the communication traffic for multi-word searches in a distributed hash table - Sei, Yuichi (2006)
In distributed hash tables, much communication traffic comes from multi-word searches. The aim of this work is to reduce the amount of traffic by using a bloom filter, which is a space-efficient probabilistic data structure used to test whether or not an element is a member of a set. However, bloom filters have a limited role if several sets have different numbers of elements. In the proposed method, extra data storage is generated when contents' keys are registered in a distributed hash table system. Accordingly, we propose a "divided bloom filter" to solve the problem of a normal bloom filter. Using the divided bloom filter, we aim to reduce both the amount of communication traffic and the amount of data storage.